Combined Analysis of Hydrogen and Oxygen 102.6 nm Emission at Mars. Issue 16 (19th August 2022) - Chaffin, Michael S.; Deighan, Justin; Jain, Sonal; Holsclaw, Greg; AlMazmi, Hoor; Chirakkil, Krishnaprasad; Correira, John; England, Scott; Evans, J. Scott; Fillingim, Matt; Lillis, Rob; Lootah, Fatma; et al.
Abstract: Water is lost from the Mars upper atmosphere to space as hydrogen and oxygen, both of which can be observed in scattered ultraviolet sunlight at 102.6 nm. We present Emirates Mars Mission Emirates Mars Ultraviolet Spectrometer (EMM/EMUS) insertion orbit observations of this airglow, resolving the independent altitude contributions of H and O for the first time. We present the first airglow modeling of the complete H and O 102.6 nm system and the first 3D azimuthally symmetric modeling of the O emission, retrieving temperatures and densities typical of northern spring. Our model reproduces the emission well above 200 km, but does not incorporate partial frequency redistribution needed to reproduce the observed O brightness at lower altitudes and on the disk. These results support future EMM/EMUS science orbit retrievals of H loss and the use of 102.6 nm observations to constrain planetary atmospheres across the solar system. Plain Language Summary: The Emirates Mars Ultraviolet Spectrometer (EMUS) on the Emirates Mars Mission (EMM) is the first Mars‐orbiting instrument capable of observing extreme ultraviolet airglow, including light at 102.6 nm. Sunlight at this wavelength is scattered by both hydrogen and oxygen in the Mars upper atmosphere. Here we present the first observations capable of detecting the independent contributions of H and O to the emission brightness as a function of altitude. O contributes brightness close to the planet, because it is more massive and therefore more tightly confined by gravity than H. Our model can reproduce the shape of the observations above 200 km altitude, and determine that the atmosphere conditions are typical for the time period observed. At lower altitudes, the model prediction is dimmer than reality because the model does not include one of the ways that O atoms scatter sunlight when the atmosphere gets dense. These results lay a foundation for EMM science orbit data analysis, which will help us understand how H and O are distributed around Mars, how much H is escaping from Mars to space today, and how the planet has evolved over the history of the solar system. Key Points: We present the first observations of 102.6 nm emission at Mars that reveal the independent contributions of hydrogen and oxygen We successfully reproduce the coronal emission with the first model to include the complete O 102.6 nm system Reproduction of observed disk O 102.6 nm emission will require incorporating additional physics into the model